SEMANTIC PROSODY OF WORDS OF EFFECTS IN INDONESIAN - Prihantoro, Prihantoro (Indonesian Journal of Applied Linguistics, 2015)
In a cause-and-effect type sentence, the choice of lexis and grammar are of crucial importance. This paper focuses on five near synonymous Indonesian lemmas indicating effect, which are: hasil, efek, konsekuensi, dampak and akibat. In Kamus Besar Bahasa Indonesia[1] (the online version of the Indonesian reference dictionary used in this study), these lemmas are described without any feature of semantic prosody. Does this mean that the prosody of these words is not important? My study has shown otherwise. I, here, have extracted cause-and-effect sentences from the PAN Localization Corpus[2] (the reference corpus employed in this study). The collocates and grammatical constructions show that the semantic prosody of hasil is flexible. However, discussion of my finding shows that the prosody for the rest of the lemmas tends to be negative. This can be seen from statistics showing lexical preferences for words with negative associations and negative grammatical constructions where the effects are negative or unexpected. This holds true the four text types in the corpus (economy, sport, science and international affairs). For this reason, I recommend that the KBBI development team should incorporate this feature in forthcoming versions of the dictionary.[1] www.daring.kbbi.co.id[2] http://www.panl10n.net/indonesia/